Determining the optimal localization of nodes in wireless sensor networks: indoor environment - العلي, هدى (Latakia University Journal -Engineering Sciences Series, 2023)
Due to development of wireless sensor networks WSN and the expanding of their uses in large field of connections, the needs of saving power are the most important issue when dealing with WSN. Many solutions have proposed to save wireless nodes energy like using different protocols to choose the best way according to many circumstances like energy, data packet loss, etc.…. In this study, we will discuss two different topologies for constructing wireless sensor networks and compare their performance due node energy using networks simulator NS2.